Glucosyltransferase CsUGT78A14 Regulates Flavonols Accumulation and Reactive Oxygen Species Scavenging in Response to Cold Stress in Camellia sinensis - Zhao, Mingyue; Jin, Jieyang; Gao, Ting; Zhang, Na; Jing, Tingting; Wang, Jingming; Ban, Qiuyan; Schwab, Wilfried; Song, Chuankui (Frontiers in Plant Science, 2019)
Glycosyltransferases (UGTs) play diverse roles in cellular metabolism by altering regulatory metabolites activities. However, the physiological roles of most members of UGTs in crops in response to abiotic stresses are unknown. We have identified a novel glycosyltransferase CsUGT78A14 in tea crops, an important economic crops, whose expression is strongly induced by cold stress. Biochemical analyses confirmed that CsUGT78A14-1 showed the highest activity towards kaempferol and is involved in the biosynthesis of kaempferol-diglucoside, whereas the product of CsUGT78A14-2, which differs from CsUGT78A14-1 by a single amino acid, was identified as 3-O-glucoside. The accumulation of kaempferol monoglucosides and diglucosides was consistent with the expression levels of CsUGT78A14 in response to cold stress, as well as in different tissues and genotypes of tea plants. Down-regulation of CsUGT78A14 resulted in reduced accumulation of flavonols, ROS scavenging capacity and finally reduced tea plant stress tolerance under cold stress. The antioxidant capacity of flavonols aglycon was enhanced by glucosylation catalyzed by CsUGT78A14. The results demonstrate that CsUGT78A14 plays a critical role in cold stress by increasing flavonols accumulation and ROS scavenging capacity, providing novel insights into the biological role of UGTs and flavonoids in plants.